The Effect of Ischemic-Reperfusion on Acute Kidney Injury Pathogenesis to the Glomerular Microscopic Appearance and Cystatin C Level in Wistar White Rat. - Annisa Wimaulia Azlin; Rachmat Hidayat; Kemas Ya'kub Rahadiyanto (HM Publisher, 2019)
Acute kidney injury (AKI) is a sudden decrease of kidney function. The incidence of AKI is increasing every year. One of the causes of AKI is the lack of blood supply to the kidneys (prerenal). At the present time, there are not many studies that report unilateral ischemic-reperfusion (UIR) duration which can cause kidney damage especially glomerulus. The aim of this study is to determine the effect of UIR duration to glomerular microscopic appearance, GFR and cystatin C produced in Wistar white rats. This study was performed in vivo by using Post-test Only Control Group Design. Unilateral Ischemic-Reperfusion was administered on the rat’s left kidney and recovery was done according to specified time. After recovery time, rat’s blood was taken, the rat was euthanized, and its kidneys were taken and stained with Picrosirius Red coloring. The kidneys were observed by using OptiLED and the photos were analyzed with ImageJ software. Blood samples were tested by ELISA to measure the cystatin C levels and the levels were converted into Larrson formula to obtain Glomerular Filtration Rate. The level of cystatin C increased along with the longer duration of UIR and compared inversely proportional to GFR which decreased along with the rise of UIR duration. Cystatin C and GFR had a significant mean difference (p<0.05) with all groups, except for the duration of the UIR group <60 minutes. The percentage of collagen obtained fluctuated but the whole group which was carried out by UIR had a significantly different collagen amount (p <0.05) with the sham-operated group. The average glomerular picture showed the addition of collagen, Bowman's capsule thickening and vascular retraction. The longer duration of UIR will worsen the kidney function. Keywords: Unilateral Ischemic-Reperfusion, Cystatin C. Glomerular Filtration Rate, Collagen Area Fraction, Glomerulus